Analisis Faktor Penentu Dalam Desain Sistem Pengendalian Unit Lembaga Keuangan - Komala Ardiyani; Muhammad Maulidin Fachrur (Fakultas Ekonomi Universitas Pekalongan, 2015)
This study examined the effect of interdependence between the units and the information asymmetry betweenthe central management and unit managers to use performance measurement unit of financial institutions anddecision delegation of authority. Data were obtained by sending questionnaires to the respondents. Therespondents of this study is the manager of the unit in the form of bank financial institutions and non-banks inthe City and County Pekalongan. Fifty (50) of the questionnaires used in data processing with the bank details of24 respondents and 26 non-bank respondents. The data is processed using multiple linear regression analysis totest the hypothesis. These results prove that the interdependence between the units significantly negativeeffect on the use of performance measurement unit shaped bank financial institutions, non-bank was notsignificant. Information asymmetry is a significant negative effect on the use of performance measurement unitshaped bank financial institutions, non-bank whereas no significant effect. Interdependence between the unitsis not significant negative towards devolution of decision authority in the form of bank financial institutions,non-bank was a significant negative effect. Information asymmetry significant positive effect on the delegationof decision authority in the form of bank financial institutions, non-bank whereas no significant effect.Keywords: Using Performance Measurement Unit; Delegation of Authority Decision On Unit; Information Asymmetry; interdependence, Financial Institutions.